Nilai Budaya dari Ritual Perkawinan Massarak sebagai Materi Pendidikan Keluarga Kristen di Mamasa - Masdariani Sidu; Frans Paillin Rumbi (Sekolah Tinggi Teologi Simpson Ungaran, 2021)
Generally, Christian education focuses on biblical preaching and church tradition. This method is correct, but it doesn't close the way for other approaches. Christian education can use different strategies to teach the Christian faith. This research focuses on the massarak marriage ritual. The researcher wants to find the cultural values contained in it. The focus of this research is the Mamasa people who live in the Nosu District, Kabupaten Mamasa. Furthermore, the researcher wants to see it from the aspect of Christian education. The authors used qualitative methods to answer the research objectives, namely data collected from observations and interviews, then the data were presented descriptively. The results showed positive values in massarak rituals, namely respect, independence, love, and solidarity. These values can be used in Christian education, of course, in dialogue with the Christian faith.